(untitled) (Bangladesh Journal of Zoology, 2016)
A study on the lynx-spiders was carried out from different areas of Khulna district of Bangladesh. Six (6) species of the genus Oxyopes Latreille were identified of which four (4) species were recorded for the first time from Bangladesh. The paper contains a description and distribution together with key to the species. Bangladesh J. Zool. 43(2): 221-238, 2015